Knowledge Management and Industry 4.0 and Open Innovation - Palacios Osma, José Ignacio; Moreno Salazar, Fabián Leandro; Morales Gómez, Karen Natalia (Ingeniería Solidaria, 2020)
Introduction: The bibliographic review that is presented is the result of the research “Open Innovation and Knowledge Management” developed at the Universidad Distrital Francisco José de Caldas, during the year 2019; where the research problem focused on establishing the relationship between Open innovation, Knowledge management and its impact on Industry 4.0, where the exchange of information and knowledge is evident, allowing for the exchange and integration of knowledge and technology in the context of co-creation in Industry 4.0. Objective: To demonstrate a Knowledge management and Industry 4.0 model that consolidates innovation processes in Colombian organizations. Methodology: A systematic mapping of information was developed, focused on the academic databases of the publications that link the concepts of Knowledge management, Industry 4.0 and Open innovation in the period 2016-2019. Conclusions: Innovation is a key factor for organizations, in particular to achieve competitiveness. For this, it is necessary to have inter institutional and intra-institutional knowledge management models, characterized by the decentralized exchange of information in the context of Industry 4.0. Therefore, it is necessary that the governance of an organization understand and facilitate the processes of opening and exchanging knowledge and information. Originality: This model allows for the convergence of different models of administration and organization ma-nagement, which must be co managers of resource management and human talent. Limitations: The model is developed from the literature review and from the experiences presented in these investigations, implying that a second stage is necessary for validation with experts.